What is the impact of Th1/Th2 ratio, SOCS3, IL17, and IL35 levels in unexplained infertility? - Ozkan, Zehra Sema; Deveci, Derya; Kumbak, Banu; Simsek, Mehmet; Ilhan, Fulya; Sekercioglu, Samet; Sapmaz, Ekrem (Elsevier Ireland Ltd, 2014)
Implantation necessitates complex interactions among the developing embryo, decidualizing endometrium, and developing maternal immune tolerance and/or alterations in cellular and humoral immune responses. Overstimulation of T helper 1 (Th1) or Th2 cytokines in systemic and local environments, alterations of the prevalence of IL17 and regulatory T cell (Treg) cytokines have also been suggested to contribute to the pathogenesis of implantation failure. We aimed to investigate the plasma levels of IL4, IL6, IL10, TNF alpha, IFN gamma, TGF beta, IL17, IL35, and SOCS3 in infertile and fertile women. This case-control study was conducted with 80 women suffering from unexplained infertility and 40 fertile women. Peripheral venous blood samples were drawn on day 21 of the menstrual cycle. The extracted plasma samples were assayed by an enzyme linked immunosorbent assay. Statistical analysis was performed using SPSS version 16.0. Our main findings were as follows: despite the significantly high IL17 and IL35 plasma levels of infertile women, IL35/IL17 ratio was significantly lower in the infertile group compared with that in the fertile group; SOCS3 plasma levels showed an inverse relation with plasma levels of all cytokines except IL35; increased plasma IL17 levels (>3.42 pg/mL) have a negative impact on fertility; TNF alpha/IL10, IFN gamma/IL10, IFN-gamma/16, and IFN gamma/IL4 ratios were significantly higher in infertile group compared with those in the fertile group. It is not possible to show the major immunological factor(s) of unexplained infertility, but our findings point out that the decreased suppressor activity of the immune system may play a role in implantation failure. (C) 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: Infertility; Implantation; IL17; IL35; SOCS3; T helper